Self-Portraits of a Truthful Liar: Satire, Truth-Telling, and Courtliness in Ludovico Ariosto’s Satire and Orlando Furioso - Ugolini, Paola (Renaissance and Reformation / Renaissance et Réforme, 2017)
Composed during the most difficult years of Ludovico Ariosto’s relationship with the Este court, the Satire are known for presenting a picture of their author as a simple, quiet-loving man, and also as a man who can speak only the truth. However, the self-portrait offered by the Satire of the author as a man incapable of lying stands in direct contrast to the depiction presented by St. John in canto 35 of the Orlando Furioso of all writers (and thus, implicitly, of Ariosto) as liars. This article investigates the relationship between such contrasting self-portraits of Ariosto, aiming to overcome the traditional opposition of satire as the mode for honest speech—and for a truthful portrayal of the author’s self—and epic as the mode for courtly flattering.